2019
DOI: 10.4067/s0718-221x2019005000416
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wood flour on the mechanical, thermal and morphological properties of poly (L-lactic acid)-chitosan biopolymer composites

Abstract: The aim of this paper was to investigate the effects of wood flour on the mechanical, morphological and thermal properties of poly (L-lactic acid) (PLA)-chitosan biopolymer composites produced by compression molding. The composites were characterized by a combination of mechanical properties, scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC). The addition of chitosan to PLA matrix reduced the tensile strength from 57,1 MPa for pure PLA to 34,3 MPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
(22 reference statements)
0
8
0
1
Order By: Relevance
“…The findings of this research show that the biocomposite material’s flexural strength fulfills the standards for cortical bone, which are 50–150 MPa [ 24 ]. Additionally, this research created a biocomposite material with a flexural modulus that met the requirements for the cortical bone’s flexural modulus, which is 0.6–2.69 GPa [ 55 ]. Additionally, the biocomposite created in this work has a higher flexural modulus than cancellous bone, which has a flexural modulus of 0.05–0.5 GPa [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The findings of this research show that the biocomposite material’s flexural strength fulfills the standards for cortical bone, which are 50–150 MPa [ 24 ]. Additionally, this research created a biocomposite material with a flexural modulus that met the requirements for the cortical bone’s flexural modulus, which is 0.6–2.69 GPa [ 55 ]. Additionally, the biocomposite created in this work has a higher flexural modulus than cancellous bone, which has a flexural modulus of 0.05–0.5 GPa [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…They reported that chitosan/cellulose membranes can be used for wound dressing as it has the potential to prevent wound based on antimicrobial capability against Escherichia coli and Staphylococcus aureus. Altuntas and Aydemir (2019) investigated effect of wood flour on the performance properties of poly (L-lactic acid)-chitosan biopolymer composites. They reported that wood flour improved all the mechanical and thermal properties of PLA-chitosan.…”
Section: Introductionmentioning
confidence: 99%
“…The better morphology of CM samples was related to the high pressure applied during processing. This pressure allows higher material compaction producing fewer voids and better wood particles wettability, which, as discussed in the following paragraphs, gave higher density values (Altuntas andAydemir 2019, Cisneros-López et al 2018). The density of the wood particles and the biocomposites are presented in Table 1.…”
Section: Morphology and Densitymentioning
confidence: 91%
“…The use of biodegradable polymers has significantly increased over the last years, especially the polylactic acid (PLA) due to its good properties such as high mechanical strength, easy processability, and a wide range of available commercial grades (González-López et al 2018, Altuntas andAydemir 2019). PLA is a semi-crystalline aliphatic polyester with applications in the agricultural, biomedical, and packaging industries (Kim et al 2007).…”
Section: Introductionmentioning
confidence: 99%